2023
DOI: 10.3390/ijms241310758
|View full text |Cite
|
Sign up to set email alerts
|

3-[N,N-Bis(sulfonyl)amino]isoxazolines with Spiro-Annulated or 1,2-Annulated Cyclooctane Rings Inhibit Reproduction of Tick-Borne Encephalitis, Yellow Fever, and West Nile Viruses

Abstract: Spirocyclic compounds containing heterocyclic moieties represent promising 3D scaffolds for modern drug design. In the search for novel anti-flaviviral agents, we have obtained a series of 3-[N,N-bis(sulfonyl)amino]isoxazolines containing spiro-annulated cyclooctane rings and assessed their antiviral activity against tick-borne encephalitis (TBEV), yellow fever (YFV), and West Nile (WNV) viruses. The structural analogs of spirocyclic compounds with a single sulfonyl group or 1,2-annulated cyclooctane ring were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…There are two general approaches to N-benzyl-1-(trimethylsilyl)-N-(methoxymethyl)methanamine I activation for corresponding yilde cycloaddition, presented in the literature. [16,28,29] This ylide can be generated either by heating with lithium fluoride in dimethyl formamide or by the action of trifluoroacetic acid in THF at room temperature. Examination of the conditions applied to azolones 1-4 e demonstrated that the use of TFA is typically more effective.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are two general approaches to N-benzyl-1-(trimethylsilyl)-N-(methoxymethyl)methanamine I activation for corresponding yilde cycloaddition, presented in the literature. [16,28,29] This ylide can be generated either by heating with lithium fluoride in dimethyl formamide or by the action of trifluoroacetic acid in THF at room temperature. Examination of the conditions applied to azolones 1-4 e demonstrated that the use of TFA is typically more effective.…”
Section: Resultsmentioning
confidence: 99%
“…[6,7] In particular, various spirocyclic derivatives incorporating five-membered heterocyclic core are of interest, since their synthetic and natural analogs exhibit a wide range of pharmacological activities, including antimicrobial, antiviral, fungicidal, antidiabetic, anticonvulsant, antitumor and other effects (Scheme 1). [8][9][10][11][12][13][14][15][16][17][18] Many methods have been developed for the synthesis of such substances. Among all of them, cycloaddition reactions occupy an important method.…”
Section: Introductionmentioning
confidence: 99%
“…These substituents can be decorated further to construct more promising molecules, given the prevalence of piperidines in approved drugs (Vitaku et al, 2014). Molecules with the triazole ring were slightly more potent, especially when an aromatic substituent was introduced into the triazole ring (1, 2, 4, 5, 10, 11) instead of carboxymethyl (3,6,12); all the carboxymethyl bearing compounds were in fact inactive. Effect of fluorination of the distal phenyl could not be established due to a high standard deviation of EC 50 for compound 2.…”
Section: Virusmentioning
confidence: 99%